2004
DOI: 10.1051/0004-6361:20040070
|View full text |Cite
|
Sign up to set email alerts
|

Wind accretion in binary stars

Abstract: Abstract. Three-dimensional hydrodynamic calculations are performed in order to investigate mass transfer in a close binary system, in which one component undergoes mass loss through a wind. The mass ratio is assumed to be unity. The radius of the mass-losing star is taken to be about a quarter of the separation between the two stars. Calculations are performed for gases with a ratio of specific heats γ = 1.01 and 5/3. Mass loss is assumed to be thermally driven so that the other parameter is the sound speed o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…However, we emphasize that many uncertainties play a role in this estimate, both in the assumed distribution functions (which are reasonable for stars in the solar neighbourhood, but not necessarily for halo stars), and in the assumed wind accretion efficiency. The latter is based on the Bondi & Hoyle (1944) prescription, whereas hydrodynamical simulations (Theuns et al 1996;Nagae et al 2004) predict typically lower accretion efficiencies. These uncertainties deserve more attention in a follow-up study (Izzard et al, in preparation).…”
Section: Fluorine Abundances In Cemp Stars From Binary Systemsmentioning
confidence: 99%
“…However, we emphasize that many uncertainties play a role in this estimate, both in the assumed distribution functions (which are reasonable for stars in the solar neighbourhood, but not necessarily for halo stars), and in the assumed wind accretion efficiency. The latter is based on the Bondi & Hoyle (1944) prescription, whereas hydrodynamical simulations (Theuns et al 1996;Nagae et al 2004) predict typically lower accretion efficiencies. These uncertainties deserve more attention in a follow-up study (Izzard et al, in preparation).…”
Section: Fluorine Abundances In Cemp Stars From Binary Systemsmentioning
confidence: 99%
“…Consequently, the canonical BHL accretion cannot adequately explain the observations of the nearest and best-studied symbiotic binary, Mira, characterized by slow wind speeds (Karovska 1997;Karovska et al 2005). Furthermore, several hydrodynamical simulations in two and three dimensions have found that the mass-accretion rate is very different from that estimated by the BHL when the wind speed is comparable to (or slower than) the orbital velocity (e.g., Bowen 1988;Theuns & Jorissen 1993;Theuns et al 1996;Ruffert 1994;Bate et al 1995;Mastrodemos & Morris 1998;Nagae et al 2004;Jahanara et al 2005;Mohamed & Podsiadlowski 2007de Val-Borro et al 2009). For instance, Theuns et al (1996) found that the mass-accretion rate in the model with a ratio of specific heats of γ=1.5 is about ten times smaller than theoretical estimates based on the BHL prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Böhm-Vitense et al 2000), transfered through its stellar wind and when on the Asymptotic Giant Branch (AGB), matter enriched in carbon and s-process elements. The level of contamination of the barium star will therefore depend on several factors, some depending on the orbital properties of the system as well as on the stellar wind velocities (Theuns et al 1996;Mastrodemos & Morris 1998;Nagae et al 2002). Because a large quantity of matter has been lost by the system when the companion evolved from the AGB phase to its present white dwarf nature, the present orbital properties of barium stars are not the original ones.…”
Section: Introductionmentioning
confidence: 99%